Decision-Making in Private Equity and Private Credit: An Integrative Review - Novelli, Elena; Pignataro, Andrea (Academy of Management Annals, 2026)
Private capital decisions—across private equity and private credit—shape innovation, firm transformation, and capital allocation. Yet, how investors decide remains underintegrated across theories and methods. Scholarship has developed along three metatheoretical traditions—economic rationality, social embeddedness, and psychological boundedness—and has relied heavily on factor–outcome designs, making it difficult to distinguish durable mechanisms from behavioral bias or context-bound artifacts. We review 936 articles spanning more than 80 years. We synthesize them into a staged, multilevel framework that maps the three logics to core modules: investors’ strategies and characteristics; decision-making cues and approaches; mechanisms; decision focus (selection, structuring, portfolio management, and exit); performance and broader implications; and external contingencies. This integrative lens organizes what is known—clarifying which factors matter, through which mechanisms, and under what conditions—and specifies how the logics that jointly govern private capital decision-making might act as complements or substitutes. In doing so, it provides a common architecture for a more cumulative research program on private capital and a template for studying judgment under uncertainty more broadly.